Evaluating the impact of geomorphological determinants and Hazards on urban expansion in Rania. (Raparin Journal of Humanities (RJH), 2024)
This study aims to evaluate the impact of geomorphological phenomena that are considered natural barriers on the expansion of the city of Rania. The study area is located in the northeast of the Kurdistan region of Iraq and in the northwest of Sulaymaniyah Governorate. Rania is located astronomically between both latitudes (36°:17: 05 - 36°: 12 :30) north and both longitudes (45°:51: 05 -°45 :54 :30) east. The study area is the administrative center of the Rania district, located in the southeast of the district. In terms of administrative units, in the north of Sarkabakan, northeast of Pshdar district, in the south of Dokan Lake, and in the west of each of the chawarqorna, Hajiyawa, and Betwata, The purpose of the research is to create a morphological stage map, geomorphological units, topography, and slope degree that are considered natural obstacles and risks to the expansion of the city of Rania. Since 1977, the area of residential units has reached about 1.18 km2, and the city has continued to expand in stages, reaching 24.74 km2 in 2022. The Kewarsh and Hajila Mountains form a natural obstacle to the expansion of the city in the northeast, northwest, and southwest directions, so the city takes a longitudinal shape. 100% of the urban area is located at an altitude of 491–749 m, and at an altitude of 750–1430 m, there are no residential units. (63.8%) of the study area has a slope of less than 5 degrees. The area of residential units reaches 88.84%, and the degree of slope is higher (35 degrees), as there is no residential area there as a result of the natural geomorphological barriers that limit the expansion of the city of Rania.